What does the minister do? On the working conditions of political leaders. (5th March 2018) - Pedersen, Lene Holm; Hjelmar, Ulf; Bhatti, Yosef
Abstract : This article contributes insight into the working conditions of political leaders based on rarely accessible high‐quality data that include unique surveys of Danish ministers, mayors, and permanent secretaries supplemented by in‐depth interviews. The results show that the classical metaphor of the leader as a puppet master being pulled by an endless number of strings also fits the ministers. Their work life is fragmented in time and space, and their time is in great demand when compared to mayors and permanent secretaries. They experience high work pressure, which comes at a cost to their personal lives. They are exposed in public life and harassed, especially on social media. The implications for the balance between the minister and permanent bureaucracy, descriptive representation as well as policy innovation and quality of decision‐making are discussed. It is concluded that stressful working conditions are likely to affect the way our democracies work.